Погребения со сложносоставными луками биритуального могильника Красная Горка салтовской культуры - Аксенов, В.С.; Михеев, В.К. (Степи Европы в эпоху средневековья, 2009)
At the Krasnaia Gorka biritual burial ground of Saltov culture in seven burials of the end of the 8th - the mid 9th cc. (3 cremations and 4 inhumations) the remains of the unequally preserved compound-complex bows, presented by a different number of horn overlays, have been found.